Efficacy of high‐dose corticosteroid in the early stage of viral acute liver failure. Issue 5 (22nd May 2013) - Fujiwara, Keiichi; Yasui, Shin; Yonemitsu, Yutaka; Mikata, Rintaro; Arai, Makoto; Kanda, Tatsuo; Imazeki, Fumio; Oda, Shigeto; Yokosuka, Osamu
<x xml:space="preserve">Abstract</x> Aim Acute liver failure (ALF) is a worldwide problem despite its rare incidence because of its extremely high mortality. There are no beneficial therapies except for emergency liver transplantation for ALF. However, in Japan where the problem of a shortage of donor livers still remains, therapies other than transplantation must be further investigated for patients with ALF. Our aim was to elucidate the efficacy of high‐dose corticosteroid (CS) in decreasing liver enzyme levels in the early stage of ALF. Methods Thirty‐one consecutive Japanese patients with viral ALF in the early stage were prospectively examined for their clinical and biochemical features and treatment responses during 2 weeks after the start of treatment. Nineteen were treated with high‐dose methylprednisolone, and 12 having clinical and biochemical backgrounds with no significant difference were treated without CS. Results The aspartate aminotransferase : alanine aminotransferase ratio became lower in patients treated with CS than in controls (P < 0.05). Fifteen of 19 patients in the CS group and eight of 12 in the control group recovered (P = 0.36). Hepatitis B viral infection and advanced liver damage at the start of treatment were associated with poor prognosis (P < 0.05). Complications during the therapy were not greater in the CS group than control (P = 0.64). Conclusion The introduction of high‐dose CS in the early stage of ALF was effective in suppressing the destruction of hepatocytes. CS‐treated patients showed slightly higher survival rates and slightly more improved liver regeneration than controls, although the differences were not statistically significant.